TOOLS OF INTELLECTUAL PROPERTY MANAGEMENT OF A HOLDING COMPANY AND ITS SUB-SYSTEMS - Nicolai N. Samoilenko (Статистика и экономика)
The concept and essence of intellectual property management are considered in the article, as well as the models, the methods and the tools of intellectual property management of holding structures. In particular, the life cycle of object of intellectual property is described, the concept "intellectual property management" is created, the most effective models of intellectual property management are revealed, and also the instruments of intellectual property management of a holding company and its sub-systems are defined.